The Influence of Numbered Head Together (NHT) Cooperative Learning Model on Student Learning Outcomes Theme 2 Subtheme 1 "Harmony in Differences" in Class VI Students at UPTD SD Negeri 124385 Pematang Siantar - Frans Warnen Horen Saruksuk; Lisbet Novianti Sihombing; Desi Sijabat (International Journal of Global Sustainable Research, 2023)
The aim of this research is to improve student learning outcomes in thematic learning Theme 2 Subtheme 1 through the Numbered Head Together (NHT) type cooperative learning model. This research was carried out at UPTD SD Negeri 124385 Pematang Siantar with the research subjects being class VI with 30 students. This type of research uses an experimental method with a One Group Pretest-Posttest Design research design. Data collection techniques are tests and documentation. Data analysis techniques are descriptive statistical tests and hypothesis testing. The research results show an increase in student learning outcomes through the Numbered Head Together (NHT) cooperative learning model. This is evidenced by the increase in student completion scores, where the average pre-test score is 60.8 and the average post-test score is 83.06, so it can be concluded that the application of the Numbered Head Together (NHT) learning model has affected the results. Student learning is said to be quite effective.